Istoriko-tipologičeskij analiz elamskogo, churritskogo i urartskogo jazykov: paralleli i raschozdenija - Chačikjan, M.L. (Gs Diakonoff)
engl. Resümee: A Historic-Typological Analysis of Elamite, Hurrian and Urartian: Divergences and Similarities